Neotectonics along the Pua fault in Changwat Nan, Northern Thailand : evidence from remote sensing and thermoluminescence dating - Kitti Khaowiset (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2007